Impacts of Monitoring and Evaluation, Active Roles of Lecturers, Classroom Interaction, and Government Policy on Teaching Productivity - Qurtubi, Achmad (BISNIS & BIROKRASI: Jurnal Ilmu Administrasi dan Organisasi, 2018)
Lecturers as university educators are main player and determinant of successful educational efforts. Their roles are getting challenged when their productivity are highlighted. They face challenges which come from three sources, i.e. university standards; (2) education measurement; (3) issue of balancing between government standards and higher education institutional plan. However, there is a gap that lecturers’ efforts in improving teaching productivity are rarely observed especially in higher education institutions. The purpose of this study is to determine whether programs that have been run by the institutions have achieved the expected goals. This study observes institutional preparation and evaluation to measure their lecturers’ roles in teaching and classroom interaction. Our study has found that Monitoring & Evaluation (M&E/Monev) and lecturers’ active role can bring impacts on teaching productivity. We have also found that attempts of lecturers and higher education institutions in complying with government education policies can improve institutional ability to develop their institutional plan.